Analysis of lameness traits and type traits in Hungarian Holstein-Friesian cattle - Gudaj, Richard; Brydl, Endre; Komlósi, István (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2012)
Lameness is an important factor for culling animals. Strong legs and feet improve herd life of dairy cows. Therefore, many countries include leg and feet conformation traits in their breeding programs, often as early predictors of longevity. In the study 609 cows from 5 farms were observed for a year for correlation between lameness and conformation traits. Among the type traits, rear leg side view (0.30), rump angle (0.18), back teat placement (0.18) and front teat placement (0.18), had the strongest associations (P < 0.05) with clinical lameness. Low leg angle, low rump angle, back and front tits pointing inside were associated with increased clinical lameness. Correlations with strength and body depth ranged from 0.12 to 0.14, indicating that heavier cows were slightly more prone to clinical lameness. Practical implementation of higher selection pressure on rear leg side view is recommended.